Perceived technology use, attitudes, and barriers among primary care nurses - Million Bimerew; Jennifer Chipps (AOSIS, 2022)
Background: In primary healthcare, health information technology has the potential to facilitate the delivery of healthcare services by improving quality of care, efficiency and patient safety. However, little is known about the uptake and technology acceptance among primary healthcare nurses. Aim: The aim of this study was to describe health information technology acceptance and use among primary healthcare nurses. Setting: Primary healthcare centres in the Western Cape. Methods: A quantitative descriptive survey was conducted with a sample of 160 nurses working in primary healthcare for more than 6 months, using a self-administered questionnaire based on the technology acceptance model constructs. Eighteen primary healthcare centres were randomly selected with a sample of 160 using nonprobability purposive sampling. Results: Ninety-three (58.1%) respondents completed the survey. Three-quarters of the respondents reported positive attitudes, positive perceptions of usefulness and ease of use towards the use of health information technology. Barriers of access and training were reported by 75%, with around half the respondents reporting poor computer and information accessing skills. Health information technology use was varied, with high ratings for seeking and using and low ratings of ability to use health information technology for patient administration and management. Health information technology use was predicted by perceptions of ease of use. Conclusion: This research presents a mixed picture of acceptance of technology among primary healthcare nurses and highlights the lack of access to computers and Internet in these settings. Contribution: This study contributes to the field of technology acceptance among primary healthcare nurses.